(untitled) (translation. a transdisciplinary journal, 2021)
It is a great pleasure to be here. I like talking in the City. I live here. I am a New Yorker. Nobody is weird in New York. I am at home. It is here in my place of employment, a great university, chat I am engaged in the losing battle of real (as opposed to sellable) institutional change. Like Anthony Pym, I too am against boycott policies as a substitute for activism. I have repeatedly taken a stand against boycott policies. I chink what we have to recognize is chat there is a double bind at work here. Like in most things, if you wane not to be a follower of boycott policies, nothing changes. Bue at the same time you have to acknowledge chat the idea chat there are no national boundaries within scholarship is simply false.